Airport concern alliance against the construction of Iloilo International Airport. - Estares, Corazon C.; Gegrimal, Denil Maria P. (2008.)
The construction of New Iloilo International Airport affected 452 families in the towns of Cabatuan, Sta. Barbara and San Miguel. the Department of Transportation and Communication (DOTC) is the government institution that is in-charge of this project, which promised to provide the affected families with free relocation site, livelihood trainings and cosultations, and prioritization in the airport employment under the 400 - million pesos Comprehensive Assistance Program (CAP) for the project Affected Families (PAF). Because of lengthy delays in negotiations over the price of the land, local government officials intervened promising the affected families with free house and lot packages, strongly urge them to agree with 65 pesos per sq meter land price. In the implementation of the airport project, the free house and lot packages were not by the local officials. As a result, the Airport Concern Alliance (ACA) was formed as initiated by Sanlakas, partido ng manggagawa and KPML. Their mobilization started a series of rallies in front of the Iloilo Provincial Capitol, expropriation proceedings and barricading the main entry points of the airport which paralyzed the construction. Because of the group's mobilization, the DOTC coordinated with the National Housing Authority (NHA) providing the affected families a free relocation site and a Php 50,000.00 housing material loan
Thesis (Undergraduate, Bachelor of Arts in Political Science)- University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Iloilo International Airport -- Construction -- Cabatuan, Iloilo